The Influence of Macroeconomics Variables, Global Crisis, and Geopolitical Situations on IDX Composite - Dyah Wahyutri; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2026)
The Jakarta Composite Index (JCI) is a key indicator of Indonesia’s capital market performance and reflects investor responses to macroeconomic conditions and global uncertainty. Rising market volatility in recent years underscores the urgency of identifying the determinants of IHSG movements. This study aims to examine the effects of macroeconomic variables and geopolitical shocks on the JCI using a quantitative approach with monthly time-series data from January 2015 to May 2025. The analysis employs multiple linear regression based on the Ordinary Least Squares (OLS) method with robust standard errors. The variables include inflation, interest rates, exchange rates, money supply (M2), gold prices, and geopolitical crisis proxies represented by dummy variables. The results show that macroeconomic factors and geopolitical crises jointly exert a significant influence on JCI fluctuations, with varying impacts across variables. These findings imply that maintaining macroeconomic stability and incorporating global risk considerations are crucial for policymakers and investors in supporting capital market resilience.